TEMA-TEMA DALAM ANTOLOGI TEKS CERPEN MAHASISWA ANGKATAN 2014 PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Lasmini, Yessi; Thahar, Harris Effendi (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study was to describe and analyze the themes in the anthology of short story texts for students of the 2014 Indonesian Language and Literature Education Study Program. This type of research is qualitative research with descriptive methods. The approach used in this study is an objective approach. The data of this study are themes in the anthology of short stories of students in the 2014 Indonesian Language and Literature Education class in the form of words, sentences, and discourses. The technique of analyzing this research data, which collects data, is classified, then analyzed based on theory. The method used is descriptive method in accordance with the research objectives. Based on the results of the study, found the themes in the anthology of short stories students in the 2014 Indonesian Language and Literature Education class were found. First, data containing physical themes with indicators of adolescent love conflict. Second, data containing organic themes with indicators of sexual scandal conflict and betrayal of husband and wife. Third, data containing social themes with indicators of economic conflict, struggles in living life, love: friendship, parent-child, and crime (murder). Fourth, data that contains selfish themes: selfishness, character and attitude which are characteristic of inner conflict. Fifth, data containing several themes (main themes and additional themes) indicators are more than one meaning. Based on the results of the study, it is hoped that it can be applied to Indonesian language lessons in class XI SMA with short story text material.Â Kata Kunci:Â tema-tema, antologi teks cerpen